Local Hemostatic Activity of Psidium guajava Leaves in Swiss Webster Mice - Vitamia, Cszahreyloren; Saputra, Angga (Pharmacology and Clinical Pharmacy Research)
Psidium guajava (P. guajava) leaves have been empirically used to stop bleeding. Tannin,one of this plantâs secondary metabolites, may contribute to this activity. However, informationregarding its pharmacologicy activity was limited. Therefore, this study was performedto evaluate local hemostatic activity of P. guajava leaves. This study used Duke method withmale Swiss Webster mice as test animals. The animals were grouped into three i.e., negativecontrol (distilled water), positive control (epinephrin), and P. guajava group. Its tail was cut(2-3 mm) and the bleeding time was calculated. Statistical analysis was performed usingKruskal-Wallis test and continued with Least Significant Different (LSD) test. The mean(SD) of bleeding time for those groups were 246.00 (22.95), 72.40 (5.55), and 88.40 (7.03),respectively. There was a significant difference between the negative control group with theother two groups, but there was not significant difference between the positive control groupand the P. guajava group. In conclusion, P. guajava showed promising local hemostatic activityand can be further developed as potential hemostatic agents.Keywords: Psidium guajava, hemostatic, bleeding time